Large-scale offshore wind production in the Mediterranean Sea. Issue 1 (1st January 2019) - Pantusa, D.; Tomasicchio, G.R.
Abstract: In recent years there has been a growing interest in offshore wind energy thanks to the various advantages it offers. The offshore wind energy is used for the production of electric energy above all in the shallow waters but different research activities and large-scale demonstrations are also under way for the deep waters with scientific and technological advances that open possibilities also for new markets such as the Mediterranean Sea. In this context, the present paper aims to estimate the large-scale offshore wind production of the Mediterranean Sea. The methodology uses an open GIS platform and considers bathymetric data, annual average wind speed data, environmental data, turbines technical characteristics and administrative information. Three depth categories have been considered. The overlap between depth categories and annual average wind speeds ranges has allowed to determine the areas potentially suitable for wind farms allocation. On the basis of optimal wind farm layouts and of the characteristic of the type of turbines considered, the theoretical maximum annual offshore wind production has been estimated for whole Mediterranean area and it is about 742 TWh/year. Moreover, for each depth category, the theoretical annual wind offshore production for each Mediterranean country has been estimated.